italian (ACME, 2020)
This paper examines Kierkegaard’s reflections on tragic, as they unfold in the first section of Either/Or, concerning aesthetics. For Kierkegaard, his adaptation of Sophocles’ tragedy realizes the aesthetic criteria which he sets down in this chapter: modern lyricism joining Greek epicism. His new arrangement of Antigone’s character becomes an answer to the crisis of modern tragedy, where the core of dramatic conflict is always threatened to shift from the aesthetic to the ethical sphere, which is incompatible with the very nature of tragedy. We briefly recapitulate Kierkegaard’s text, and analyze it along two main outlines: we try and find the point of intersection between Kierkegaard’s biography and his dramatic adaptations of Antigone and the other female characters observed in Either/Or; and connecting The Tragic in Ancient Drama Reflected in the Tragic in Modern Drama with the two following chapters of Either/Or, Silhouettes and The Unhappiest One, we try to disclose its consistent, organic architectonics.